Modularity Framework as a New Software Framework in Enhancing Modularity in Open Source Projects - Emanuel, Andi Wahju Rahardjo; Mustofa, Khabib (2009)

(untitled)
In this paper a new Open Source Software Framework called Modularity Framework is proposed and analyzed for the first time. Study by several researchers such as Dekoenigsberg and Gurbani have identified that modularity is one of the key success factors of Open Source Projects, but how modularity should be achieved in these projects are not clearly understood. The primary components of the proposed Software Framework, which are Software Design Patterns and Software Components, are analyzed against some parameters currently attributed to software modularity such as module’s size, number of modules, complexity, cohesion, and coupling / dependency (fan in, and fan out). The result of the analysis shows that the composition of these Design Patterns combined with Software Components (interfaces and abstract classes) in a form of Software Framework called Modularity Framework is highly feasible.